Perancangan Bisnis UMKM Rumahan Berbasis Digital untuk Meningkatkan Aksebilitas Pasar di Kab. Mandailing Natal - Ayu Maydani Hsb, Alisya; Annas, Firdaus; Fitri, Annisa (Yayasan Lembaga Studi Makwa, 2023)
Designing a digital-based home-based MSME business is a strategic step in increasing market accessibility, especially in Mandailing Natal Regency which has great local economic potential but limited market access. This research aims to design a digital-based business model using open-source platforms such as openchart to support the digitalisation of MSMEs. MSMEs often face challenges in marketing their products widely due to limited access and digital capabilities. This research was conducted with a Research and Development (R&D) approach using the Waterfall model is a classic model that is systematic, sequential in building software. The name of this model is actually ‘Linear Sequential Model’. This model is often referred to as the ‘classic life cycle’ or waterfall method. This model belongs to the generic model in software engineering and was first introduced by Winston Royce around 1970 so it is often considered ancient, but it is the most widely used model in Software Engineering (SE). This model takes a systematic and sequential approach. It is called waterfall because the stages passed must wait for the completion of the previous stage and run sequentially. The results showed that the implementation of openchart-based e-commerce can increase the market accessibility of MSMEs by up to 40%, expand consumer reach, and increase the marketing efficiency of local products. Openchart is proven as a user-friendly and efficient platform for the digitalisation of MSME businesses in Mandailing Natal, Openchart-based digitalisation increases market accessibility by expanding consumer reach, both locally and nationally.